Controllable synthesis of Cu–Ni core–shell nanoparticles and nanowires with tunable magnetic properties. Issue 42 (5th May 2016) - Guo, Huizhang; Jin, Jiarui; Chen, Yuanzhi; Liu, Xiang; Zeng, Deqian; Wang, Laisen; Peng, Dong-Liang
Abstract : The controlled epitaxial growth of Ni shells on Cu cores provided selectively exposed surfaces and morphologies and tunable magnetic properties. Abstract : Cu seeds were used to direct the epitaxial growth of Ni shell to form Cu–Ni core–shell cubes, tetrahexahedrons and nanowires. The controllable epitaxial growth of Ni shells on Cu cores provided selectively exposed surfaces and morphologies as well as tunable magnetic properties.